Parasitic Strip Loaded Dual Band Notch Circular Monopole Antenna with Defected Ground Structure - P Syam Sundar; Sarat K Kotamraju; B T P Madhav; M Sreehari; K Raghavendra Rao; L Prathyusha; Y Pravallika (Institute of Advanced Engineering and Science, 2016)
In this article a parasitic strip loaded monopole antennas are designed to notch dual and triple bands. The designed models are constructed on one side of the substrate material and on the other end defected ground structures are implemented. The basic antenna comprises a tuning stub and a ground plane with tapered shape slot as DGS. Another model is constructed with circular monopole radiating element on front side and similar kind of ground structure used in the basic rectangular tuning stub antenna. To create notched bands with tuning stubs, two symmetrical parasitic slits are placed inside the slot of the ground plane. The basic model is of the rectangular stub notching triple band and the circular tuning stub antenna notching dual band. Dual band notched circular tuning stub antenna is prototyped on FR4 substrate and measured results from vector network analyzer are compared with simulation results of HFSS for validation.